2013
DOI: 10.1016/j.devcel.2013.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropilin 1 Cytoplasmic Domain Is Required for VEGF-A-Dependent Arteriogenesis

Abstract: SummaryNeuropilin 1 (NRP1) plays an important but ill-defined role in VEGF-A signaling and vascular morphogenesis. We show that mice with a knockin mutation that ablates the NRP1 cytoplasmic tail (Nrp1cyto) have normal angiogenesis but impaired developmental and adult arteriogenesis. The arteriogenic defect was traced to the absence of a PDZ-dependent interaction between NRP1 and VEGF receptor 2 (VEGFR2) complex and synectin, which delayed trafficking of endocytosed VEGFR2 from Rab5+ to EAA1+ endosomes. This l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
210
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 191 publications
(231 citation statements)
references
References 46 publications
18
210
3
Order By: Relevance
“…Moreover, mutants lacking endothelial NRP1 or NCCderived SEMA3C had similar defects. These observations suggest However, the importance of this pathway in vivo has so far only been demonstrated for arteriogenesis (57). In contrast, the results presented here show that mice lacking VEGF-A binding to NRP1 have normal OFT remodeling, even in the absence of NRP2.…”
Section: Discussioncontrasting
confidence: 77%
“…Moreover, mutants lacking endothelial NRP1 or NCCderived SEMA3C had similar defects. These observations suggest However, the importance of this pathway in vivo has so far only been demonstrated for arteriogenesis (57). In contrast, the results presented here show that mice lacking VEGF-A binding to NRP1 have normal OFT remodeling, even in the absence of NRP2.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, the early postnatal development of the retina vasculature, a process that is largely VEGF driven, was also dramatically impaired in Frs2α −/− mice. Finally, a study of arteriogenesis using a hindlimb ischemia model also demonstrated a profound retardation of arterial network formation that is comparable to that seen in other genetic mice models with impaired VEGF-dependent activation of MAPK signaling (16,22). Taken together, these data point to a critical role played by endothelial FRS2α in vascular development, angiogenesis, lymphangiogenesis, and arteriogenesis.…”
Section: Discussionsupporting
confidence: 63%
“…In these experiments, we manipulated the availability of VEGF, the abundance of RECK and KDR kinase activity with the SU5416 inhibitor (Sakao and Tatsumi, 2011), we quantified VEGF signaling readouts (KDR, AKT and ERK1/2 phosphorylation levels) and measured the abundance of RECK and KDR ( Fig. S9I-J′; Koch et al, 2011;Lanahan et al, 2013;Zachary, 2003). We found that knockdown of RECK impairs VEGF signaling by reducing pKDR and pAKT levels without affecting the abundance of pERK (Fig.…”
Section: Introductionmentioning
confidence: 98%